Geoarchaeology and tropical forest soil catenas of northwestern Belize. (2nd January 2018) - Beach, Tim; Ulmer, Austin; Cook, Duncan; Brennan, Michael L.; Luzzadder-Beach, Sheryl; Doyle, Colin; Eshleman, Sara; Krause, Samantha; Cortes-Rincon, Marisol; Terry, Richard
Abstract: New research on soil catenas under old growth tropical forest in NW Belize aims to understand soil formation, long-term human impacts, and slope stability over time. We studied areas with intensive ancient Maya impacts from 3000 to 1000 years ago and those with little ancient impact to compare how ancient land-use influenced slopes after about 1000 years of stable tropical forest cover. We characterized the physical, chemical and chronological characteristics of soils at crest/shoulders, backslopes, footslopes, and depression locations, analyzing typical soil parameters and carbon isotopes (δ 13 C) in dated and undated sequences. Several of the footslope and depressions sites preserved evidence of buried paleosols with increased δ 13 C dating (by four new AMS dates and three others we reported earlier) from the Maya Classic period, with high amounts of soil organic matter from C4 species in ecosystems where only a few C4 species occur today. Most crest/shoulders and backslopes had no evidence for increased δ 13 C, though some crests and mid-slope sinks preserved evidence of ancient Maya impacts. The observation that steep slopes preserved no evidence of C4 species inputs may mean that ancient Maya land use maintained forest reserves here. Alternatively, ancient Maya land uses caused slope erosion, with the δ 13 C signatures detected today resulting from more recent soil development under forest and soil re-formation over the last millennium. Additional evidence that these soils are recent in age includes elevated CaCO3, Sr, and low soil magnetic susceptibility, showing less leaching compared with older soils in our study. Other human impacts on soils include increased concentrations of Fe and Mn, terracing, and further evidence of substantial topsoil erosion in antiquity.